066. Sleeve Gastrectomy Decrease of TNF-a and Increase TGF-a Gene Expression in the Abdominal Aorta of Rats with Obesity and Diabetes Mellitus - Saputro, Addy; Prasetyo, Sigit Adi; Shobirin, Muhammad Ali; Rozy, Abdul Mughni (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p066, 2024)
Background : Sleeve gastrectomy (SG) is one option to significantly reduce body weight while also protecting the cardiovascular system by controlling hyperglycaemia and inflammatory markers. Secretion of tumour necrosis factor (TNF)-? could induce inflammation, meanwhile, the transforming growth factor-? (TGF-?) are anti-inflammatory cytokines, both of which play a role in the process of atherosclerosis. This study aimed to analyse the effect of SG procedure on TNF-? and TGF-? gene expression in the abdominal aorta of obese and DM rats. Method : Fifteen rats were divided into 3 groups: lean-non-DM rats model (C1 group), obese-DM rats model (C2 group), and obese-DM rats model underwent SG (T group). Before and 10 days after the SG procedure, rats’ body weight and fasting blood glucose (FBG) were measured. Ten days after the procedure, TNF-? and TGF-? gene expression were also evaluated by PCR. Results : At the end of the study, mean body weight, FBG levels, and TNF-? gene expression in the C1 group (231.80±4.32 gram; 68.60±2.07 mg/dL; 1.01±0.01 rfu) and T group (232.00±5.33 gram; 114.40±3.20 mg/dL; 1.97±0.57 rfu) were significantly lower than in C2 group (264.60± 3.28 gram; 271.00±6.89 mg/dL; 224.12±47.59 rfu). TGF-? gene expression was found to be considerably higher in T group (25.62 ± 3.03 rfu) compared to C1 group (1.05 ± 0.01 rfu) and C2 group (1.63 ± 0.21 rfu). Conclusion: SG could decrease body weight and FBG, as well as TNF-? gene expression, and increase TGF-? gene expression in the abdominal aorta of rats with obesity and DM.